Effects of Occupational Stress and Frequency of Lifting Heavy Loads on Low Back Pain in Health Workers: A Meta Analysis - Ahmad Syauqi Mubarok; Argyo Demartoto; Bhisma Murti (Journal of Epidemiology and Public Health, 2022)
Background: Health workers have a high risk for experiencing symptoms of disorders of the musculoskeletal system such as pain, injury, trauma, and other disorders. According to the World Health Organization (WHO), work-related musculoskeletal disorders or commonly called work-related musculoskeletal disorders (WRMDs) are injuries that include various inflammatory disorders or degenerative diseases associated with pain or functional disorders in the body.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, Population: Health workers. Intervention: High stress and high frequency of heavy lifting. Comparison: Low stress and low frequency of weight lifting. Outcome: Back pain. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles “low back pain” “risk factors” “determinants” “predictors” AND “health workers” The articles included were full-text English with a cohort and cross-sectional study design from 2016 to 2021 and reported the adjusted odds ratio (aOR) in the multivariate analysis. The selection of articles was done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 5 cohort and 10 cross-sectional studies, ten articles included nurses as research respondents, four articles included overall medical personnel, and one article included ambulance workers. Research locations are in Denmark, Saudi Arabia, China, Japan, Malaysia, Iran, Brazil Italy, Australia, Yemen, Estonia, and Ethiopia with medical workers who have low levels of job stress (aOR= 2.52; 95% CI= 2.15 to 2.96; p< 0.001) and it can be concluded that medical workers with frequent heavy lifting have a risk of experiencing back pain by 2.01 times compared to medical workers with infrequent weight lifting frequency (aOR= 2.01; 95% CI 1.23 to 3.18; p = 0.003).Conclusion: Medical workers with high levels of job stress and frequent heavy lifting are at risk for back pain. Keywords: back pain, stress, weight lifting. Correspondence:Ahmad Syauqi Mubarok. Masters Program of Public Health Sciences, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: syauqimubarok39@gmail.com. Mobile: 085741144248.